Different Radial Growth Responses to Climate Change of Three Dominant Conifer Species in Temperate Forest, Northeastern China - Wang, Hui; Ning, Yangcui; Liu, Chunlan; Xu, Peng; Zhang, Wentao (Frontiers in Forests and Global Change, 2022)
We conducted dendroclimatological study on three dominant conifer tree species, Pinus koraiensis, Larix olgensis, and Picea jezoensis, in northeastern China for a better understanding of climate change impacts on temperate forest growth, by discussing the radial growth relationships of these tree species and projecting their radial growth trends under the future climate change scenarios. Based on the tree-ring samples collected from the upper altitude of Changbai Mountain, ring width chronologies were built to examine the growth relationships, and regression equations were established to project the future growth of the species under future climate change projected by the five general circulation models (GCMs) and four representative concentration pathway (RCP) scenarios. Although both temperature and precipitation showed varying degrees of relationships with growth of these three tree species, the limiting climate factors were species-specific. The tree-ring growth of P. koraiensis was limited by the summer temperature and precipitation at the end of growth, namely, significant positive correlations with the current July temperature and the previous September precipitation. Growth of L. olgensis was limited by the temperature before growing season, for its chronology was negatively correlated with the current February and previous December temperature (p < 0.05). The climatic conditions before and after growing season seemed to be the limiting factors of P. jezoensis growth, which was negatively correlated with the current February to April temperature and the current September temperature (p < 0.05), and positively correlated with the current August precipitation (p < 0.05). Under the gradual increasing of temperature predicted by the five GCMs and four RCP scenarios, the radial growth of P. Koraiensis will relatively increase, while that of L. olgensis and P. jezoensis will relatively decrease comparing to the base-line period (1981–2010). The specific growth–climate relationships and the future growth trends are species dependent. P. Koraiensis was the more suitable tree species for the forestation to maintain the sustainable forest in Changbai Mountain.